The Role of Sports and Health Physical Education Teachers on School Dental Health Business Services: Peran Guru Pendidikan Jasmani Olahraga Dan Kesehatan Terhadap Pelayanan Usaha Kesehatan Gigi Sekolah - Inandy Rambu Kadunga; Melkisedek O. Nubatonis; Apri A. Manu; Emma Krisyudhanti (Dental Therapist Journal, 2020)
The School Dental Health Business (UKGS) is an integral part of the School Health Business (UKS) which carries out planned dental and oral health services for students, especially elementary school students (STD) within a certain period of time, which is carried out continuously through the UKS package, namely the UKS package. minimal, standard package and optimal package. Teachers are people who help others learn, by training, explaining, giving lectures, regulating discipline and evaluating students' abilities. Teachers can act as counselors and give instructions. In this case, Sports and Health Physical Education teachers have a more important role in UKGS services to students than other school communities. Because Sports and Health Physical Education teachers know more about health sciences, anatomy, physiology and handling injuries compared to teachers other. Because they know more about health, Sports and Health Physical Education Teachers have a more important role and are expected to be involved in UKGS activities. The purpose of this study was to determine the role of sports and health physical education teachers on school dental health business services. The method in this research is descriptive method. The results showed that the results of the questionnaire distribution to determine the role of sports teachers in UKGS services were in good criteria as many as 10 people (71.5%), in promotive efforts were in good criteria as many as 10 people (71.5%), preventive on criteria good as many as 10 people (71.5%) and simple curative on good criteria as many as 10 people (71.5%). It was concluded that the role of sports teachers in providing UKGS services, both promotive, preventive and curative efforts were in good criteria. Usaha Kesehatan Gigi Sekolah (UKGS) adalah bagian integral dari Usaha Kesehatan Sekolah (UKS) yang melaksanakan pelayanan kesehatan gigi dan mulut secara terencana pada siswa terutama siswa Sekolah Tingkat Dasar (STD) dalam suatu kurun waktu tertentu,diselenggarakan secara berkesinambungan melalui paket UKS yaitu paket minimal,paket standar dan paket optimal. Guru adalah orang yang membantu orang lain belajar,dengan melatih, menerangkan,memberi ceramah, mengatur disiplin dan mengevaluasi kemampuan siswa. Guru dapat berperan sebagai konselor dan pemberi instruksi. Dalam hal ini,Guru Pendidikan Jasmani Olahraga dan Kesehatan mempunyai peran yang lebih penting dalam pelayanan UKGS terhadap siswa-siswi dibandingkan masyarakat sekolah lainnya.Karena guru Pendidikan Jasmani Olahraga dan Kesehatan lebih mengetahui tentang ilmu kesehatan, anatomi,fisiologi dan penanganan pada cedera dibandingkan dengan guru yang lainnya. Karena lebih mengetahui tentang kesehatan,maka Guru Pendidikan Jasmani Olahraga dan Kesehatan mempunyai peran yang lebih penting dan diharapkan terlibat dalam kegiatan UKGS. Tujuan penelitian ini adalah untuk mengetahui peran guru pendidikan jasmani olahraga dan kesehatan terhadap pelayanan usaha kesehatan gigi sekolah. Metode dalam penelitian ini adalah metode deskriptif. Hasil penelitian menunjukkan bahwa dari hasil pembagian kuesioner untuk mengetahui peran guru olahraga dalam pelayanan UKGS berada pada kriteria baik sebanyak 10 orang (71,5%), dalam upaya promotif berada pada kriteria baik sebanyak 10 orang (71,5%), preventif pada kriteria baik sebanyak 10 orang (71,5%) dan kuratif sederhana pada kriteria baik sebanyak 10 orang (71,5%). Disimpulkan bahwa Peran guru olahraga dalam melakukan pelayanan UKGS, baik upaya promotif, preventif dan kuratif berada dalam kriteria baik.